PRESENCE OF ORGANIC POLLUTANTS IN THE SÃO FRANCISCO RIVER AND ITS COMPARTMENTS - Torres, Isabela Claret; Horn, Adolf Heinrich (Geochimica Brasiliensis, 2020)
There has been great concern about the presence of organic pollutants in the environment. These types of compounds can be found in different types of habitats and have long term and deleterious effects on all living beings. The main objective of this study was to verify the presence of organic pollutants in different compartments of the São Francisco river. Fourteen sites were sampled since right after its springs till marginal lagoons in Pirapora City. The fine sediment was subject to the soxhlet extraction. The extracts were measured in a spectrophotometer in the absorbance range of 589 nm, which correspond to a yellow spectrum that correspond to the extraction of the organic pollutants. The organic matter of the sediments was measured. There was a positive correlation between organic matter content and the absorbance in the yellow color. However, both organic matter content and absorbance did not correlate with the distance from the spring. Even though was not possible to measure which organic pollutants were present in the sediments of the different compartments of the São Francisco river, the results of this study clear indicates the presence of these compounds in the samples. The correlation of the organic matter content and the absorbance showed that the organic matter is a important constituent in the sequestration of the organic pollutants. More studies should be conducted to determine which types of compounds are present in these sediments and if there is transfer of these organic pollutants in the aquatic food chain.